An optimized active disturbance rejection approach to fan control in server. (October 2018) - Zheng, Qinling; Ping, Zhan; Soares, Simone; Hu, Yu; Gao, Zhiqiang
Abstract: As more and more massive data storage drives are used in super high density, the power used to cool the servers has become an increasingly large component of the total power consumption. Therefore, improving server cooling efficiency has become an essential requirement in data centers. However, because the thermal dynamics of the server system has characteristics such as nonlinearity, significant inter-loop coupling, and continuously fast-changing/unknown workload disturbances, these pose huge challenges to control engineers and data center architect engineers. To address the above concerns, this paper presents an active disturbance rejection control based decoupling control algorithm for flash storage systems and CPUs in a one-unit (1U) server to simultaneously improve fan power consumption efficiency and regulate the server components' temperature to avoid downgraded performance caused by overheating. In the study, a benchmark system is established based on the Samsung Mission Peak (MP) server where the thermal characteristics and existing solutions are both systematically evaluated. Performance of the design concept is proven in both simulation and a hardware testbed. With the proposed control solution, experiment results show that the temperature overshoot is greatly eliminated, temperatures are more tightly controlled, and the drive throttling rate are greatly decreased. Furthermore, the proposed method is shown to be able to save up to 45% energy versus a PID controller, save about 77% energy versus dynamic fan speed control method, and save about 98% energy versus native fan speed control.